The Impact of Artificial Intelligence Tools for Financial Risk Analysis and Accounting Decision-Making: Commercial Banks as A Model (Global Scientific Review, 2024)
The research aims to examine the impact of artificial intelligence tools on financial risk analysis and accounting decision-making in commercial banks. It investigates how these tools can enhance financial risk analysis, improve the accuracy of financial forecasts, and refine accounting decision-making processes. The study employs a descriptive analytical approach and utilizes a questionnaire method. The research sample includes managers, department heads, and accountants from Iraqi private commercial banks that are registered on the Iraqi stock market . The study yielded several significant findings. Notably, it revealed a high impact of artificial intelligence tools on accounting decision-making. Additionally, there is a noted integration between artificial intelligence and accounting systems within these banks. The participants expressed strong agreement regarding the challenges and opportunities associated with the implementation of artificial intelligence in their operations